Assessment of genetic diversity in rabi sorghum landraces using D2 statistics - P V, Rajappa; P U, Krishnaraj; N G, Hanamratti; Bagewadi , Basavaraj; C M, Nawalagatti; A, Anisha; R, Madhusudhana (Journal of Cereal Research, 2024)
We used D2 statistics to evaluate the diversity among 91 rabi sorghum landraces including 5 checks. The analysis of variance revealed that except for the number of green leaves at maturity, the genotypic variances for all traits were significant. The 96 lines were grouped into 7 clusters where cluster I was the largest containing 80 genotypes followed by cluster II with 8 genotypes, cluster III with 4 genotypes and the remaining 4 were solitary clusters. Based on the cluster mean values, cluster V was superior for grain yield, panicle width, panicle weight and test weight, while cluster IV was noted the best for early flowering and cluster IV was good for SPAD at boot leaf and maturity stage. Based on the inter cluster distances the genotypes belonging to the clusters separated by high genetic distance genotypes from cluster IV and V (B35 and IC420956) could be used in hybridization programme for obtaining a wide spectrum of variation among the sergeants. Among the 14 characters studied panicle length (25.4%) followed by panicle weight (15.3%) and test weight (11.1%) contributed the most to the genetic divergence of the genotypes.